EVALUASI HASIL GRAFTING SEMBILAN KLON KOPI ROBUSTA DENGAN BATANG BAWAH LOKAL - Dibyo Pranowo; Handi Supriadi (Jurnal Tanaman Industri dan Penyegar, 2013)
Productivity of Robusta coffee in Indonesia were classified as low of about 685 kg/ha/year, due to did not use the superior clones and their propagation technique conducted by seeds. Efforts to address these issues are the using of high yielding superior seed (above 1,000 kg/ha) and then were propagated by grafting. The objective of this research was to evaluate the success rate and growth of grafted plants arised from nine clones of Robusta coffee with Sukabumi local rootstock. The study was conducted in a Greenhouse of Pakuwon Research Station, Indonesian Industrial and Beverage Crops Research Institute, Sukabumi. A randomized block design with 9 treatment of grafting combination and 3 replication were used in this study. The nine of treatment as follows: (1) BP 42 + local, (2) BP 969 + local, (3) BP 306 + local, (4) BP 436 + local, (5) BP 913 + local, (6) BP 534 + local, (7) BP 239 + local (8) BP 430 + local, and (G9) BP 358 + local. The results showed that the plant height, leaf number, leaf area, number of branches, and grafting success rate of BP 430 + local at 5 months after grafting (MAG) more higher than other grafting combination.